Tanggung Jawab Hukum Pelaku Usaha Pelayanan Kesehatan Tradisional: Studi Systematic Literature Review dalam Perspektif UU No. 17 Tahun 2023 - Teguh Adi Partama; Repelita Witri; Ida Bagus Tatwa Yatindra; Marsudi Dedi Putra (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
This study aims to evaluate and synthesize the legal responsibilities of traditional health service providers under Law No. 17 of 2023 on Health. Using a qualitative approach with a Systematic Literature Review (SLR) design, the research identifies regulatory developments and legal practices relevant to traditional health services in Indonesia. Data collection involved online databases such as Science Direct, PubMed, and Google Scholar, using keywords like “legal responsibility,” “traditional health services,” and “Health Law No. 17 of 2023.” Samples were purposively selected based on inclusion criteria, including publications from 2023 to 2025 explicitly discussing legal issues in traditional health services.The study employed a systematic protocol comprising selection guidelines, quality criteria, and data extraction formats. Thematic analysis was used to identify key patterns such as forms of legal responsibility, mechanisms for patient protection, and standards for traditional health practices. The findings reveal that Law No. 17 of 2023 provides a more comprehensive legal framework by regulating administrative obligations, civil responsibilities, and criminal sanctions for traditional health service providers. Additionally, the law strengthens patient protection mechanisms through quality standardization, practice licenses, and service transparency. Despite its limitation in not conducting field studies and potential bias from online literature, the research process upheld scientific integrity and academic transparency. The study significantly contributes to understanding the relevance of traditional health regulations in legal practice in Indonesia and serves as a foundation for future policy development.